Experiment with the Harp Scalar Systems: The Example of the Adungu Harp in Uganda - (:unkn) unknown (My University, 2022)
Stringed instruments such as harps allow musicians to easily experimentwith scalar systems. The instrument is regularly subject to innovationsthat affect the harpist’s making and tuning. The adungu harp in Ugandais a good example; since the 1950s, the influence of popular musichas seen its constituent parts adapted to the needs of musicians. Thefirst transformation is the addition of extra strings (from 5 to 12) toincrease the range of the instrument and to change its tuning and thus“play traditional music or rumba” (interview with artist Leo Palayeng,May 2019). Recently, the artist Ssewa Sewa has patented the janzi, adouble-necked harp with 22 strings tuned to two different scales, onediatonic (Western) and one pentatonic (African). Finally, the set-up of amicrophone in the sound box is becoming more and more common forlive performances. Through the example of various innovations, we willlook back at the historical and sociological conditions that led to thesetransformations.
Keywords: African Research